Cigarette smoking, miR-27b downregulation, and peripheral artery disease : insights into the mechanisms of smoking toxicity - Pereira-da-Silva, Tiago (2021)
Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https://creativecommons.org/licenses/by/4.0/).